Factors causing stunting in pregnant women and its prevention efforts: Public Health Perspectives - Yumi Abimulyani; Yuliana Yacinta Kainde; Mardho Tillah Minggele (Oshada, 2024)
This study aims to identify the factors causing stunting in pregnant women and the preventive efforts made from a public health perspective. Stunting in infants is a significant health issue in Indonesia, with its causes often related to maternal nutrition, health status, and access to healthcare services. The research employs a quantitative method with a cross-sectional survey design. Data was collected through questionnaires distributed to 180 pregnant women registered at community health centers and hospitals. Descriptive and inferential statistical analysis was used to identify the relationship between the causes of stunting and prevention efforts. The results indicate that factors such as poor nutritional status, very young or very old maternal age, and limited access to adequate healthcare significantly contribute to infant stunting. Furthermore, health education programs and the provision of additional food supplements positively impacted the prevention of stunting. This study suggests the need for enhanced prevention efforts through broader education on the importance of maternal nutrition and better access to quality healthcare services to reduce the prevalence of stunting in Indonesia.